'Berlin Does You Good': Experimental Art, Place Marketing and the Urban Public Sphere in 1980s West Berlin. (August 2021) - Smith, Briana J.
Abstract : This article analyses the relationship of mutual benefit that formed between West Berlin's local government and experimental artists in the 1980s. In 1978 the West Berlin parliament established a grant programme to support independent artists operating in what was referred to as the 'free scene'. The grants were intended to support the goal of restoring the city's status as a capital of artistic innovation. Soon after, the local tourism office also featured these independent artists within a new place marketing strategy focused on raising the 'experiential value' of the city's cultural offerings. But as this article shows, experimental artists were also using city grants to pursue alternative agendas focused on engaging with local populations in urban space. Through these projects, experimental artists extended the spirit of participatory democracy flourishing within the city's counter-cultural enclaves to broader areas of the city.